Political and educational springboard or straitjacket? Theorising post/human subjects in an age of vulnerability. Issue 2 (3rd March 2016) - Ecclestone, Kathryn; Goodley, Daniel
Abstract : Contemporary discourses of social justice in education, disability, mental health, social policy and feminist studies are refracted increasingly through concerns about psychological and structural vulnerabilities created by the crises of late capitalism. Focusing on developments in British social policy generally and educational research specifically, this paper uses the authors' contrasting perspectives on two discernible discourses of vulnerability emerging in these contexts. One elevates the recognition of collective vulnerability as a springboard for new conceptualisations of resistance that disrupt materialist narratives of the human subject as a coherent, unified and rational agent of history. A second discourse offers a materialist understanding that locates vulnerability as both driver and product of a 'therapeutic culture', arguing that a psycho-emotional focus for vulnerability offers a diminished and ineffective subjectivity that belies rhetorics of resistance. These contrasting perspectives generate and emerge simultaneously from new understandings of the human subject. The paper evaluates the implications of using vulnerability to frame expectations of human subjects for everyday educational practices and relationships. It concludes by suggesting empirical questions that need exploring.